Efficacy of a family intervention in grief complicated by couple breakup in primary care - Medina Martínez, Sara Minerva; Sánchez Rodríguez, Rosa Maria; Garrido Pérez, Silvia María Guadalupe; Avalos-García, María Isabel; De la O León , Cesar Augusto; Castillo-Orueta, María Luisa (Horizonte Sanitario, 2024)
Objective: To evaluate the effectiveness of a family intervention in grief complicated by a couple breakup.Materials and method: Research with a mixed intervention approach in three stages (diagnosis-implementation-evaluation). In the first, an observational, cross-sectional, descriptive study was carried out, with a simple random sample with replacement n=99. Field's "Romantic Breakup Distress Scale" and Smilkstein's family APGAR were applied, with prior informed consent. Five families with complicated grief and family dysfunction were included. Methods and techniques of working with family were used. In the third stage, a quasi-experimental design was used with pretest and posttest of complicated grief and family APGAR. SPSS V25 was used to capture and analyze data, with descriptive and analytical statistics with Student's t test.Results. They were women 81.8%, with age Ⱦ=34.19-29 37.4%, high school 37.4%, separated 59.6%, divorced 49.4%. With complicated grief 14%, family dysfunction 13%. Families with complicated grief were dysfunctional 53.8%. Risk factors: conflict in paternal-filial subsystem, addictions, economy. Protective factors: religious, artistic, educational and medical groups. The actions focused on cognitive-behavioral-emotional intervention. In pretest/posttest evaluation, complicated grief presented a mean difference of Ⱦ=8.500, ŝ± 8.925, and 95% CI: Li: 3.347 Ls:13.653, with student's t=3.564 and df=13 and p value=0.003, statistically significant, mean difference for family Apgar of Ⱦ= 3.357 with ŝ±1.946, 95% CI: Li:2.234, Ls:4.481 with student's t=6.456 and df=13, p value=0.001, statistically significant.Conclusions: The effect of the family intervention modified complicated grief and improved family dynamics and functionality.  Keywords: Family Practice; Prolonged Grief Disorder; Divorce; Spirituality; Single-Parent Family.